Dynamics of heavy metals migration in the soil as a consequence of military actions - Petrushka, Kateryna; Petrushka, Ihor; Holdrych, Artur (Видавництво Львівської політехніки, 2024)
The military operations in Ukraine have consequences for the biosphere, which is negatively affected by the hostilities, causing its destruction and degradation, – soils. It is currently impossible to fully assess the impact of military and terrorist actions on the environment due to the lack of accurate information. The shelling of civilian and strategically important objects in Ukraine created synergistic conditions for the environment to accumulate and enter through leaching from the soil a large amount of heavy metals into surface water. Accordingly, this leads to mass degradation of not only the soil environment, but also the hydrosphere and plant life. The entry of potentially toxic elements (PTE) into the environment, soil and plants is accompanied by their oxidation and other chemical processes. Soil sampling was carried out by the method of a concentric circle, in the canter of which is the source of pollution, which allows us to assess the degree of distribution of potentially toxic elements depending on the depth of the well. In our research on the content of heavy metals in the soil during the shelling of Lviv and 6 months later, XRF and ICP analyzes of soil samples. The results of the analysis of the content of heavy metals in the soil after 6 months show that the concentration of cadmium is reduced by two times; copper and nickel, respectively, 3 and 3.5 times; lead+ and chromium – twice. It is known that heavy metals do not undergo decomposition processes, but can only be redistributed between natural environments. They tend to concentrate in living organisms, causing various pathologies.
Keywords: military affected area; heavy metals; soil pollution; plants; migration of heavy metals in the soil